Lowering blood pressure effect of Apium graviolens (seledri) and Orthosipleon stamineus benth (kumis kucing) in mild and moderate hypertension (Faculty of Medicine Universitas Indonesia, 2002)
In Indonesia Apium graviolens and Orthosiphon stamineus benth have been used to as traditional medicines to lower blood pressure. Since at present time is avaiLable as a combination of those phytopharmaca in the market, therefore, it is necessary to conduct a study to evaLtnte the ffictivity and side effects of those phytopharmaca toward hypertensive subjects. A randomized double blind conftolled trial was conducted at area of Monica - Jakarta in South of Jalarta from July-untiL 29 October 2001 toward mild and moderate hypertensive subjects. The first group (72 subjects) received phytophanmaca (TensigardÂ® which contains Apium graviolens and Orthosiphon stamineus benth) 3 x 250 mg, whiLe the second grottp (70 subjects) had Amlodipine I x 5 mg. Obseruation were conducted for 12 weelcs, and the parameter observed wÃ¨re systolic and diastolic blood pressure (SBP and DBP), plasma lipid, blood glucose before and after treatment, and electrolyte with nvo week intervals. The Resuhs revealed that the phytopharmaca treatment for 12 weel<s lowered SBP and DBP equivalent to Amlodipine (SBP 24.72 t 1.63 mm4g vs 26.27 + 2.18 mmHg; P > 0,05; DBP 10.00 t0.96 mmHg vs 9.49 t 1.37 ntmHg; P> 0.05). Phytopharmaca treatment for 12 weel<s did not influence plasma eLectolyte, as well blood glucose Levels. There was not asignificant side effects noted for both phytopharmaca and Amlodipine during the study period. [n conclusion, the trial reveals that the phytophnrmaca lowered systolic and diastolic blood pressure equivalent with Amlodipine among mild and moderate hypertensive subjects. During the study period there was not a significant side effect noted. (Med J Indones 2002; 11: 195-201)Keywords: blood pressure, phytopharmaca, side effect, plasma electrolytes